Effect of tailoring on weight loss among young adults receiving digital interventions: an 18 month randomized controlled trial. Issue 4 (19th March 2021) - Napolitano, Melissa A; Whiteley, Jessica A; Mavredes, Meghan; Tjaden, Ashley Hogan; Simmens, Samuel; Hayman, Laura L; Faro, Jamie; Winston, Ginger; Malin, Steven; DiPietro, Loretta
Abstract: Weight loss outcomes among young adults in technology-based programs have been equivocal. The purpose of this study was to deliver digital weight loss treatments to young adults and examine the 6, 12, and 18 month effects on weight loss. Young adults with overweight/obesity ( N = 459; 23.3 ± 4.4 years) were recruited from two university sites and randomly assigned to receive through Facebook and text messaging either personalized (TAILORED; n = 150) or generic (TARGETED; n = 152) weight loss information, messages, and feedback or general healthy body content (e.g., body image, sleep; CONTROL; n = 157). The study was powered to detect a 2.1-kg difference at all time points with the primary outcome being 18 months. There was no overall effect of treatment group on 6, 12, or 18 month weight loss ( p s = NS). However, at 6 months, those in TAILORED who were highly engaged (completing >66%) lost more weight compared to CONTROL (−2.32 kg [95% confidence intervals: −3.90, −0.74]; p = .004), with the trend continuing at 12 months. A significant baseline body mass index (BMI) by treatment group interaction ( p = .004) was observed at 6 months. Among participants in the lowest baseline BMI category (25–27.5 kg/m 2 ), those in TAILORED lost 2.27 kg (−3.86, −0.68) more, and those in TARGETED lost 1.72 kg (−3.16, −0.29) more than CONTROL after adjusting for covariates. Among participants with a BMI between 27.5 and 30 kg/m 2, those in TAILORED lost 2.20 kg (−3.90, −0.51) more than participants in TARGETED. Results did not persist over time with no treatment interaction at 12 or 18 months. Initial body weight should be considered when recommending weight loss treatments for young adults. More intensive interventions or stepped care approaches may be needed for young adults with obesity. Abstract : Few large-scale weight loss studies have specifically focused on young adults. Young adults have not been as successful in weight loss clinical trials as their older adult counterparts. This study is an 18 month randomized controlled trial comparing two digital weight loss programs adapted for young adults (one with personalized material and the other with generic material) to a control group. There were no differences in weight loss between the groups at any time point when looking at the entire sample. However, we found that initial body mass index (BMI) interacted with treatment group such that those young adults in the lowest BMI category who received one of the two digital weight loss programs lost more weight than the control group. We also found that of participants who were highly engaged (specifically completing at least 66% of the materials), those in the personalized group lost more weight than the control group at 6 and 12 months, along with a similar advantage over those receiving the generic materials at 12 months. The findings indicate that young adults with obesity (BMI >30) may need a stepped care or precision medicine approach that involves greater intensity and contact.